Sterilizer Reliability Analysis Using Reliability Block Diagram Based on Failure Identification Through Fault Tree Analysis - Bahri, Syamsul; Fatimah, Fatimah; Muhammad Jalil, Saifuddin; Amri, A; Ilham, Muhammad (Malikussaleh University, Aceh, Indonesia, 2022)
A sterilizer is a pressurized steam vessel used to boil palm oil. The condition of the sterilizer at PT .X often emits steam at the door and body of the stew. Throughout 2020, there were 12 critical components that were frequently damaged, such as ball valve, actuator, exhaust valve, packing door, elbow, condensate nozzle, liner, pipe, condensate valve, strainer valve, pipe flange, and packing flange. Fault Tree Analysis is an analysis tool that graphically translates the combinations of errors that cause system failures. Reliability Block Diagram is a diagramming method for showing how reliability components contribute to the success or failure of a complex system. Based on the results of the failure calculation using fault tree analysis, the probability of failure of the horizontal sterilizer component is the ball valve 12.2%, exhaust valve 10.9% actuator 6%, door packing 0.24%, elbow 0.24%, condensate nozzle 4.8%, liner 8.61%, 0.25% pipe, 0.21% condensate valve, 4.4% filter valve, 0.22% pipe flange and 0.27% packing flange. The reliability value of the horizontal sterilizer from the calculation using the reliability block diagram is 85.69% if it operates for 8 hours, 62.93% if it operates for 27 hours, 39.6% if it operates for 54 hours, 13.34% if it operates for 117 hours. o'clock. o'clock. o'clock. hours and 1.81% when operating for 234 hours. To maintain reliability above 60%, the preventive maintenance schedule is: Every 80 hours of operation a door packing inspection is carried out. Every 234 hours of operation, elbow tubing and flanges are checked. Every 300 hours of operation, a pipe inspection is carried out. Every 450 operational hours an inspection is carried out on the ball valve, condensate nozzle, liner, actuator, and exhaust valve. Every 30 hours of operation, valve condensate, filter valves and packing flanges are checked.